Numerical Simulation on the Cavitation Flow of High Speed Oblique Water Entry of Revolution Body. (17th January 2019) - Mu, Qing; Lv, Yipin; Wang, Kangjian; Xiong, Tianhong; Yi, Wenjun
Abstract : To explore the effects of water entry angle on the cavitation flow field of high-speed revolution body, based on the finite volume method, VOF (Volume of Fluid) multiphase model, Schnerr-Sauer cavity model, SSTk - ω turbulence model, and dynamic mesh method, numerical simulation for modeling the oblique water entry of revolution body at high speed is performed. The evolution laws of cavity shape, motion characteristics, and hydrodynamic characteristics of revolution body at different water entry angles are analyzed. The results show that the numerical calculation method can effectively simulate the change of cavity shape during the water entry of the revolution body. With the increase of water entry angle, the uplift of liquid level decreases in the positive direction of the open cavity and increases in the negative direction. The angle of water entry has little effect on the velocity of the revolution body. The larger the angle of water entry, the greater the peak pressure and the faster the pressure decay at the moment of water entry.